A cross-sectional analysis of symptom severity in adults with influenza and other acute respiratory illness in the outpatient setting - VanWormer, Jeffrey J (BioMed Central, 2014)
BACKGROUND: Acute respiratory infections (ARIs) are common in outpatient practice, and the severity of symptoms contributes to the overall burden of illness. We examined the association between a subjective symptom severity score, demographic and clinical characteristics, and presence of laboratory-confirmed influenza among central Wisconsin adults who sought care for ARI during four influenza seasons. We hypothesized that adults with laboratory-confirmed influenza would rate their symptoms as more severe relative to adults without influenza, and vaccinated adults with influenza would rate symptoms as less severe than those who were not vaccinated. METHODS: Patients with acute respiratory illness, including feverishness or cough symptoms ≤ 7 days duration, were prospectively enrolled and tested for influenza by reverse transcription polymerase chain reaction (RT-PCR) during influenza seasons 2007–08 through 2010–11. Perceived severity was self-rated during the enrollment interview for eight symptoms, on a scale of 0 (absent) to 3 (severe). Scores for each symptom were summed to generate a combined severity score ranging from 1 to 24 for each individual. The association between influenza test result and severity score was examined using linear regression. RESULTS: There were 2,374 individuals included in the analysis, including 324 with RT-PCR confirmed influenza. The mean symptom severity score was 12.3 (±4.1) points, and the most common symptoms were cough (92%), fatigue (91%), and nasal congestion (84%). In the final adjusted model, influenza infection was the strongest independent predictor of higher severity score, with a mean increase of 1.7 points compared to those who were influenza negative (p < 0.001). Among adults with influenza, the association between influenza vaccination and symptom severity was modified by age (p < 0.001). In adults ≥ 65 years old with RT-PCR confirmed influenza, symptom severity was 31% lower in those who were vaccinated as compared to those who were not vaccinated. CONCLUSIONS: Influenza is associated with more severe symptoms of acute respiratory illness. The association between influenza vaccination and reduced symptom severity in older adults should be confirmed and explored further in other populations and seasons.